A Systematic Review of Multisystem Inflammatory Syndrome in Children Associated With SARS-CoV-2 Infection. Issue 11 (November 2020) - Kaushik, Ashlesha; Gupta, Sandeep; Sood, Mangla; Sharma, Seema; Verma, Shikha
Abstract : Background: Recently, severe manifestations associated with coronavirus disease 2019 (COVID-19) called multisystem inflammatory syndrome in children (MIS-C) have been recognized. Analysis of studies for this novel syndrome is needed for a better understanding of effective management among affected children. Methods: An extensive search strategy was conducted by combining the terms multisystem inflammatory syndrome in children and coronavirus infection or using the term multisystem inflammatory syndrome in children in bibliographic electronic databases (PubMed, EMBASE, and CINAHL) and in preprint servers (BioRxiv.org and MedRxiv.org ) following the Preferred Reporting Items for Systematic Reviews and Metaanalyses guidelines to retrieve all articles published from January 1, 2020, to July 31, 2020. Observational cross-sectional, cohort, case series, and case reports were included. Results: A total of 328 articles were identified. Sixteen studies with 655 participants (3 months–20 years of age) were included in the final analysis. Most of the children in reported studies presented with fever, gastrointestinal symptoms, and Kawasaki Disease-like symptoms. Sixty-eight percent of the patients required critical care; 40% needed inotropes; 34% received anticoagulation; and 15% required mechanical ventilation. More than two-thirds of the patients received intravenous immunoglobulin and 49% received corticosteroids. Remdesivir and convalescent plasma were the least commonly utilized therapies. Left ventricular dysfunction was reported in 32% of patients. Among patients presenting with KD-like symptoms, 23% developed coronary abnormalities and 26% had circulatory shock. The majority recovered; 11 (1.7%) children died. Conclusions: This systematic review delineates and summarizes clinical features, management, and outcomes of MIS-C associated with SARS-CoV-2 infection. Although most children required intensive care and immunomodulatory therapies, favorable outcomes were reported in the majority with low-mortality rates. Abstract : Supplemental Digital Content is available in the text.